Some Small Native Freshwater Fish Recommended for Mosquito and Midge Control in Ornamental Ponds - William H. Kern, Jr. (EDIS)
This publication is intended to help anyone interested in ponds or mosquito control to identify, select, collect, and stock small native fish species that would be useful in controlling mosquito populations. This document is Fact Sheet ENY-670, a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2004.